1995
DOI: 10.1523/jneurosci.15-01-00477.1995
|View full text |Cite
|
Sign up to set email alerts
|

Human trks: molecular cloning, tissue distribution, and expression of extracellular domain immunoadhesins

Abstract: Using molecular cloning techniques, human homologs of the known members of the trk family of neurotrophin receptors have been cloned and sequenced. Overall, there is a high degree of similarity between the human sequences and those from other mammals; however, there are differences in splicing patterns. There are two spliced forms of the extracellular domain of trkC in the human, a finding that has not been described in other species. In contrast, fewer spliced forms were detected of the intracellular domains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
282
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(302 citation statements)
references
References 21 publications
17
282
1
1
Order By: Relevance
“…Brain-derived neurotrophic factor (BDNF) (Barde et al, 1982;Leibrock et al, 1989) (Nakagawara et al, 1994). In this study we have investigated the mRNA expression profile of the third member of the neurotrophin receptor tyrosine kinase family, trkC, a receptor for neurotrophin-3 (NT-3) (Lamballe et al, 1991) which is involved in the survival of subpopulations of neural crest and placodederived sensory neurons (Ernfors et al, 1994 (Shelton et al, 1995) which was identical to that of our clone in the transmembrane region. Initial Northern blot analysis showed that levels of trkC mRNA were below the detection limit in most samples.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Brain-derived neurotrophic factor (BDNF) (Barde et al, 1982;Leibrock et al, 1989) (Nakagawara et al, 1994). In this study we have investigated the mRNA expression profile of the third member of the neurotrophin receptor tyrosine kinase family, trkC, a receptor for neurotrophin-3 (NT-3) (Lamballe et al, 1991) which is involved in the survival of subpopulations of neural crest and placodederived sensory neurons (Ernfors et al, 1994 (Shelton et al, 1995) which was identical to that of our clone in the transmembrane region. Initial Northern blot analysis showed that levels of trkC mRNA were below the detection limit in most samples.…”
mentioning
confidence: 60%
“…A relapsing stage 1 tumour showed a relatively low level of trkC expression (no. 24, Figure 2 the human trkC receptor (Shelton et al, 1995 (Hoehner et al, 1995). It was found that the more differentiated tumour cells stained most intensely for trkC but there was no significant correlation with tumour stage or patient prognosis.…”
mentioning
confidence: 99%
“…BDNF was selectively sequestered during exercise using a specific immunoadhesin chimera (TrkB-IgG, R&D System, Minneapolis, MN), which comprises the extracellular domains of human TrkB and the Fc domain of immunoglobulin G (IgG), and has been shown to specifically antagonize BDNF action (Shelton et al, 1995). Infusion of TrkB-IgGs was achieved by coupling them to microbeads (Lumaflour Corp., Naples, FL), which we have previously used as a reservoir for the successful delivery of viable inhibitors into the hippocampus (Vaynman et al, 2003).…”
Section: Bdnf Blockingmentioning
confidence: 99%
“…TrkB.T2 does not appear to have signaling ability and has not been found in humans [74]. TrkB 95 , though lacking the catalytic kinase domain, still retains some signalling ability of its own [75].…”
Section: B Cell Malignanciesmentioning
confidence: 97%